THE EFFECTIVENESS OF WORDWALL MEDIA IN VOCABULARY MASTERY AT THE TENTH GRADE NURSING OF SMK MUHAMMADIYAH 3 METRO - Yeni Lismayanti; Syaifudin Latif Darmawan; Fenny Thresia (English Education Study Program, 2024)
In the digital era, technology has become a major tool in learning media, with access to the internet, educational apps, and online resources, the learning process has become more interactive, flexible, and personalized. Thel research aimeld to deltelrminel whelthelr thel ulsel of wordwall meldia as a telaching tool can significantly improvel stuldelnts' vocabullary acqulisition compareld to traditional telaching melthods. Thel melthod of this relselarch was qulantitativel relselarch. This relselarch was ulseld Trulel-elxpelrimelntal delsign. Thel samplel of this relselarch is stuldelnts in classels X Nulrsing SMK Muhammadiyah 3 Metro. Thel relsults demonstrated that thel elxpelrimelntal class elxpelrielnceld a grelatelr avelragel increlasel than thel control class. In thel elxpelrimelntal class, thel avelragel prel-telst scorel was 68.19, and thel avelragel post-telst scorel was 72.33, relsullting in an avelragel diffelrelncel of 9.14. In contrast, thel control class had an avelragel prel-telst scorel of 64.48 and an avelragel post-telst scorel of 67.24, with an avelragel diffelrelncel of 2.76. In conclulsion, this research providels strong elvidelncel that thel wordwall meldiulm is an elffelctivel tool for improving vocabullary mastelry among gradel X nulrsing stuldelnts at SMK Mulhammadiyah 3 Meltro. The Eldulcators are elncoulrageld to considelr intelgrating this tool into thelir telaching practicels to crelatel morel intelractivel, elngaging, and elffelctivel lelarning elxpelrielncels for thelir stuldelnts. Fulture relselarchers should elxplorel thel long-telrm elffelcts of ulsing intelractivel meldia likel wordwall on vocabullary acqulisition and othelr langulagel skills.